Ethical leadership creating and sustaining an ethical business culture - Leigh, Andrew 1972- (Kogan Page, 2013)
" The demand from society for organizations to be ethical and responsible is growing, and the cost of irresponsible behavior is often huge. Unethical action can dramatically affect the future of a company or destroy it all together.Ethical Leadership shines a light on the role of both culture and ethics in organizations by making the issues more transparent, accessible and above all, connected. Business leaders are now accountable for showing that they have the correct ethical policies and culture in place. Cultural and behavioral change consultant Andrew Leigh focuses on the fact that ethical culture is manifest in the actual behavior and attitudes of all staff, rather than in policy documents.While there are very few absolutes when it comes to ethics, there are clear ways to be a responsible leader, and Ethical Leadership is full of practical strategies, case studies and action points which will help leaders to improve and manage ethical culture in their organizations"..